OPTIMALISASI PENGELOLAAN DANA ZAKAT DALAM PENGENTASAN KEMISKINAN PADA KAMPUNG ZAKAT TERPADU DI DESA SUMBERSALAK, LEDOKOMBO, JEMBER - Indahwati, Diana Putri; Dhofir Catur Bashori; Miftahul Hasanah (I'THISOM : Jurnal Ekonomi Syariah, 2025)
This study aims to analyze the optimization of the management of zakat funds in poverty alleviation in the integrated zakat village in Sumbersalak Village, Ledokombo District, Jember Regency. Effective management of zakat funds and in accordance with sharia principles is expected to be a strategic solution in reducing poverty rates through a community empowerment approach. The method used in this study is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that the management of zakat in integrated zakat villages included aspects of planning, distributing and empowering mustahik productively. Programs such as skills training, business capital assistance, and economic assistance have a positive impact on improving the welfare of the community. Nevertheless, there are still obstacles such as limited funds, human resources, and program evaluations that have not been optimal. By strengthening institutions, synergy between parties, and sustainable supervision, zakat management can be more optimal and contribute significantly in poverty alleviation.